2021
DOI: 10.1038/s41598-021-94238-w
|View full text |Cite
|
Sign up to set email alerts
|

Entropy production and mixed convection within trapezoidal cavity having nanofluids and localised solid cylinder

Abstract: The entropy production and mixed convection within a trapezoidal nanofluid-filled cavity having a localised solid cylinder is numerically examined using the finite element technique. The top horizontal surface moving at a uniform velocity is kept at a cold temperature, while the bottom horizontal surface is thermally activated. The remaining surfaces are maintained adiabatic. Water-based nanofluids ($$\text {Al}_2\text {O}_3$$ Al … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Alnaqi et al (2020) studied the natural convection and entropy generation in a cubical cavity and observed that total entropy fairly increased with an increase in Rayleigh number until a certain value, when it then rose significantly. Similar studies have also been carried out (Bondareva et al, 2017;Hussein et al, 2016;Yang et al, 2021;Zhang et al, 2021;Ishak et al, 2021;Oztop et al, 2017). Natural convection in Saltbox roof is analysed for a hot climate region, with the aim of helping designers improve the thermal comfort in such conditions.…”
Section: Introductionmentioning
confidence: 81%
“…Alnaqi et al (2020) studied the natural convection and entropy generation in a cubical cavity and observed that total entropy fairly increased with an increase in Rayleigh number until a certain value, when it then rose significantly. Similar studies have also been carried out (Bondareva et al, 2017;Hussein et al, 2016;Yang et al, 2021;Zhang et al, 2021;Ishak et al, 2021;Oztop et al, 2017). Natural convection in Saltbox roof is analysed for a hot climate region, with the aim of helping designers improve the thermal comfort in such conditions.…”
Section: Introductionmentioning
confidence: 81%
“…Similarly, the related dimensional quantities are expressed by u , v , T and p respectively. Reynolds number, Grashof number, Richardson number, and Prandtl number ( Pr ) are the non-dimensional governing parameters appeared respectively, which are defined by the following relations (6) as: The following relationships (7) – (10) can be used to determine the thermos-physical properties of the nanofluid (Al 2 O 3 -water) using mixing law theory [29] ,…”
Section: Problem Definitionmentioning
confidence: 99%
“…Hence, extensive investigation on trapezoidal enclosure is required to build more effective heating and cooling systems in future. Only a few investigations in past focused on mixed convective flow in a lid-driven trapezoidal chamber [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] . All those studies along with geometric conditions (e.g., sidewall inclination angle, γ and tilt angle, θ ), working fluids, governing parameters (e.g., Ri , Re and Grashof number, Gr ) and numerical methods are summarized in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Ravnik et al [37] studied natural convection in a cubic enclosure with a heated elliptical cylinder. Ishak et al [38] numerically analyzed entropy generation in a classic trapezoid filled with alumina/water nano-fluid and an implemented immobile circular cylinder using the finite element method. Mebarek-Oudina et al [39] studied the characteristics of a hybrid nano-fluid MHD flow in an annulus between a trapezoid and a rotating cylinder with a zigzagged wall.…”
Section: Introductionmentioning
confidence: 99%